Faktor-faktor yang mempengaruhi intensi pembelian kendaraan listrik di Indonesia (GEMA EKONOMI, 2023)
Seeing the environmental conditions that are increasingly worrying day by day, many kinds of technological innovations have been carried out to overcome this issue. One of them is the creation of electric vehicles to reduce environmental issues that are happening now. There are many studies looking for factors in the intention to purchase electric vehicles. This study aims to determine what factors influence purchase intentions in Indonesia. This study uses SPSS and AMOS SEM analysis. There are several factors that show a significant effect and there are several factors that do not. These factors include a sense of environmental responsibility, environmental values, environmental knowledge, perceptions of environmental advertising, perceptions of electric vehicles, and purchase intentions